A Scenario-Based Decision-Support Framework for Affordability-Oriented Urban Regeneration Through Public–Private Partnerships - Lucia Della Spina (Sustainability, 2026)
Over recent decades, housing affordability challenges have become increasingly complex as a result of economic and social transformations affecting access to adequate housing. Alongside traditionally vulnerable groups, new population segments have emerged that face increasing difficulties in accessing the housing market despite not qualifying for public housing programmes. Against this background, the progressive reduction in public resources has made it necessary to adopt alternative intervention models capable of mobilising private capital without compromising social equity objectives. Accordingly, Public–Private Partnerships (PPPs) are increasingly regarded as suitable instruments for supporting social housing interventions, although significant challenges remain in balancing affordability objectives and financial viability. Rather than proposing a new financial appraisal model, this study develops a planning-oriented scenario-based decision-support framework that supports the comparative evaluation of alternative Public–Private Partnership (PPP) configurations for affordability-oriented urban regeneration. Financial appraisal is integrated as one component of a broader planning and housing policy decision-support process. The methodology is applied to a case study in Southern Italy, in a district characterised by settlement criticalities, unmet housing demand, and limited public resources. The case study illustrates how scenario-based comparative appraisal can support planning and housing policy decisions by identifying the governance and implementation conditions under which affordability objectives and financial feasibility can be jointly pursued.